La rentabilité salariale des parcours d'études non linéaires - Ines Albandea (Nantes Université, 2017)
In France, more and more young people are interrupting their post-secondary education even if re-enter higher education implies all kinds of costs. Yet, little attention has been given so far to the effect of temporary dropout on future wages. This research highlights the difficulties in measuring the net effect of schooling discontinuities. On the one hand, temporary interruption seems to have a positive effect on wages. On the other hand, labour market tend to reward more diploma of people with linear path than diploma of people who left postsecondary education. In fact, people who interrupted temporary their education could have better characteristics like greater motivation that employers value in the labour market. Moreover, it is possible that jobs that interrupter held during his interruption is expected to be more valuable than the pre-graduation experience acquired by non-interrupter, even after controlling for the level of work experience.